Preliminary Assessment of a Historic Masonry Church Strengthened by Reinforced Concrete Elements During 1927–1930. the Case of Recoleta Dominica Basilica in Santiago, Chile - Barrientos-Monsalve, M (Springer Science and Business Media B.V., 2024)
One of the main issues of heritage preservation in highly seismic areas is the compliance between structural safety requirements and conservation criteria. In Chile, from the beginning of the 20th century to the present time, 17 megathrust earthquakes have shocked the country around the Chilean central valley. The most recent and destructive of them, the 2010 (8.8 Mw) Maule earthquake, damaged 52% of Historic Monuments and Pinteresque Zones around the Central Valley, where 60% of them were URM churches. In this context, the paper focuses on the analysis of the efficient seismic performance of a representative example of a neoclassical Basilica, the Recoleta Dominica in Santiago (1853–1883), and an unusual case in the country that has shown a satisfactory seismic response along history. The investigation suggests that its efficient seismic performance can be explained mainly by avant-garde retrofit work carried out early in the 1930s, based on a strengthening system composed of reinforced concrete (RC) beams and columns, which has avoided its collapse and thus, its cultural loss. A preliminary assessment of the seismic behavior before and after the retrofitting interventions, through the Linear Cinematic Analyses of the main mechanisms observed following the 1985 and 2010 earthquakes was carried out. In opposition, the current structural interventions criterion on architectural heritage suggests non-destructive methods and techniques. Further investigations in this field may provide inputs to establish a more comprehensive analysis of this issue, as defining appropriate interventions criterion on this architectural and RC strengthening typologies. © 2024, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Historic Churches; Linear Cinematic Analyses; Reinforced Concrete Strengthening Typologies; Unreinforced Masonry structures